Designing multimedia a visual guide to multimedia and online graphic design - Lopuck, Lisa (Peachpit Press, 1996)
If you're interested in being part of the booming field of multimedia, this beautifully illustrated volume shows you how. Its concept-to-product approach is highly visual: with stunning, full-color samples of actual multimedia projects. Title structure, user interface, software dynamics, and many other factors that affect design decisions are explained in detail.